Visualization Analysis of Research Hotspots and Trends in Electrochemical Machining Based on Literature Big Data - Feng Ji; Ye Kong (Engineering Reports)
ABSTRACT Based on the big data of literature in the field of Electroforming processing, knowledge mapping and bibliometric methods are used in this article to conduct a visual analysis of the research hotspots, development trends, and research networks in this field. The results indicate that: (1) Research in the field of Electroforming processing has been shown to have a significant upward trend, reflecting the high attention and investment devoted to Electroforming technology by both academia and industry. Outstanding research performance in this field has been demonstrated by China, South Korea, and the United States, while core research forces in this domain are institutions such as the Chinese Academy of Sciences, Nanjing University of Aeronautics and Astronautics, Dalian University of Technology, and Seoul National University. (2) The co‐occurrence analysis of keywords has revealed the close connection between Electroforming processing technology and hot technologies like resistance and memory, showcasing the broad application prospects of Electroforming processing technology across numerous fields, including electronics, materials, and biomedicine. (3) International cooperation in the field of Electroforming has been characterized by diversification and deepening, resulting in the formation of multiple cooperation networks encompassing Asia and Western Europe, North America and Asia, European scientific research powers, and emerging market countries. (4) Attention has continued to be paid to Electroforming technology in terms of precision and multidisciplinary integration. Driven by the increasing demand in aerospace, automobile manufacturing, and electronic circuits, innovations in Electroforming processing technology are constantly being made, thereby promoting the advancement of science and technology as well as the development of new materials.